“Pushing the Boundaries: Breakthrough in Research Culture” A Report on the First Research Conference of the Institute of Medicine (IOM-RECON25) - Paneru, Hem Raj; Shilpakar, Olita; Shrestha, Lava; Lakhey, Paleswan Joshi (Journal of Institute of Medicine Nepal, 2025)
The First Research Conference of the Institute of Medicine (IOM) was held on 12th July 2025 in Kathmandu with the theme "Pushing the boundaries: breakthrough in research culture" It provided a platform for researchers, clinicians, students, and institutional leaders from IOM’s constituent and affiliate colleges to collaborate, share findings, and inspire innovation, recognizing the need for locally tailored evidence-based healthcare. The event, organized by the Research Department of IOM, featured 52 presentations, including two keynote speeches, 17 invited thematic lectures, two panel discussions, and 31 free paper presentations. Expert chairpersons guided these sessions, facilitating the presentations and discussions. The conference represented a significant step in enhancing IOM’s academic quality and research capabilities. It encouraged collaboration and innovation while promoting evidence-based medical practices.